2018
DOI: 10.1186/s12888-018-1594-1
|View full text |Cite
|
Sign up to set email alerts
|

The Research and Evaluation of Antipsychotic Treatment in Community Behavioral Health Organizations, Outcomes (REACH-OUT) study: real-world clinical practice in schizophrenia

Abstract: BackgroundOutpatient facilities, such as community behavioral health organizations (CBHOs), play a critical role in the care of patients with serious mental illness, but there is a paucity of “real-world” patient outcomes data from this health care setting. Therefore, we conducted The Research and Evaluation of Antipsychotic Treatment in Community Behavioral Health Organizations, Outcomes (REACH-OUT) trial, a real-world, prospective, noninterventional observational study of patients with mental illness treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…A strength of the current study is that the completion rate of 95.4% is one of the highest observed for a 1-year real-world study in schizophrenia. 3841 This supports the overall effectiveness and tolerability of PP3M, although it may also be reflective of the requirement for patients to be stabilized prior to inclusion in this study. The high completion rate is consistent with the extremely high proportion of both patients (82%) and physicians (94%) who were satisfied with PP3M treatment at the end of the study.…”
Section: Discussionsupporting
confidence: 63%
“…A strength of the current study is that the completion rate of 95.4% is one of the highest observed for a 1-year real-world study in schizophrenia. 3841 This supports the overall effectiveness and tolerability of PP3M, although it may also be reflective of the requirement for patients to be stabilized prior to inclusion in this study. The high completion rate is consistent with the extremely high proportion of both patients (82%) and physicians (94%) who were satisfied with PP3M treatment at the end of the study.…”
Section: Discussionsupporting
confidence: 63%
“…Most included studies used a study design that adjusted for differences between study cohorts, which limits the risk of bias due to confounding. Three studies did not report a method of multivariable adjustment, including two retrospective cohort studies [ 50 , 52 ] and one pragmatic trial [ 53 ]. These studies reported on the likelihood of being hospitalized [ 50 , 53 ], the likelihood of having an ER visit [ 53 ], and adherence [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies did not report a method of multivariable adjustment, including two retrospective cohort studies [ 50 , 52 ] and one pragmatic trial [ 53 ]. These studies reported on the likelihood of being hospitalized [ 50 , 53 ], the likelihood of having an ER visit [ 53 ], and adherence [ 52 ]. In all cases, the studies’ point estimates fell within the range of the other studies reporting on these outcomes, and therefore it is unlikely that descriptive studies that did not adjust for confounding materially impacted this review’s conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The mean size for all included studies was 4338.1067, and range of studies sizes were 22 to 70 969. These studies included 16 randomized controlled trials (Alphs et al 2016;Bai et al 2007; Barnett et al 2012;Bartzokis et al 2012;Bozzatello et al 2019;Buckley et al 2015;Detke et al 2014;Green et al 2015;Keks et al 2007;Leatherman et al 2014;Macfadden et al 2010;Malla et al 2016;Rosenheck et al 2011;Subotnik et al 2015;Weiden et al 2009Weiden et al , 2012, 11 prospective cohort studies (Aykut 2019;Bellido et al 2008;Conley et al 2003;Devito et al 1978;Joshi et al 2018b;Kim et al 2008;Moore et al 1998;Olivares et al 2009;San et al 2013;Schreiner et al 2014;Tavcar et al 2000), and 48 retrospective cohort studies (Anderson et al 2017;Ascher-Svanum et al 2013;Barrio et al 2013;Baser et al 2015;Bitter et al 2013;Chan et al 2015;Emsley et al 2008;Fan et al 2018;Foster et al 2017;Greene et al 2018;Grimaldi-Bensouda et al 2012;Haro et al 2007;…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of these, five studies(Barrio et al 2013;Joshi et al 2018b;Leatherman et al 2014;Levitan et al 2016;Petri c et al 2019) reported improvements in PSP scores among LAI as compared with oral users. However, four studies(Bozzatello et al 2019;Joshi et al 2018b;Leatherman et al 2014;Rosenheck et al 2011) reported no differences in LAI and oral users as observed on the PSP scale. In pooled analysis of four studies(Barrio et al 2013;Bozzatello et al 2019;Petri c et al 2019;Rosenheck et al 2011), LAIs were no different than orals in improving PSP mean scores (n = 529, 95%CI = À0.162 to 1.335, P = 0.125; s 2 = 0.513, I 2 = 90.9%, Q = 33.136, df = 3, P < 0.001).…”
mentioning
confidence: 99%